2014
DOI: 10.7763/ijtef.2014.v5.392
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics and Voluntary Segments Disclosure among the Largest Firms in Nigeria

Abstract: Abstract-The aim of this study is to gain more insights in the disclosure practices among the largest public listed companies in Nigeria, by examining the associations between firm characteristics and the extent of voluntary segments disclosure on IFRS 8 Operating Segments by using a sample of 76 companies. The results document that firm size and industry type have positive association with voluntary segments disclosure. In addition, negative association is observed between firm listing age, growth, return on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
7
13
3
5
Order By: Relevance
“…Wallace (2004) investigates the impact of firm characteristics on disclosure in annual reports of Spanish companies using regression analysis and disclosure was found significantly positive to firm size. Also (Ibrahim 2014) investigates the association between firm size and voluntary segment reporting in Nigeria and the result indicates significant positive relationship. Suwaidan, Omari and Abed (2007) asserted that company size might have a substantial effect on the level of disclosure.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Wallace (2004) investigates the impact of firm characteristics on disclosure in annual reports of Spanish companies using regression analysis and disclosure was found significantly positive to firm size. Also (Ibrahim 2014) investigates the association between firm size and voluntary segment reporting in Nigeria and the result indicates significant positive relationship. Suwaidan, Omari and Abed (2007) asserted that company size might have a substantial effect on the level of disclosure.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They urged that form of <IR> must be tested across different sizes of the organization in order to gauge the applicability. Therefore, company size has been found to be one of the prominent factors in influencing voluntary disclosure (Uyar et al, 2013;Ghasempour and Yusof, 2014;Ibrahim, 2014). Frias-Aceituno et al (2013) concluded that the decisions to undertake <IR> are prevalently influenced by the size of the company, its management bodies, and its gender diversity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the company commit to reporting qualified earning with the little discretion, the companies could increase the segment disclosure as a signal to investors. Segment disclosure decisions are not only due to changes in standards and company characteristics (Lucchese & Carlo, 2012;Pardal & Morais, 2012;Saarilouma, 2013;Ibrahim, 2014), but also manager's policies (Abbas, Habbe, & Pontoh, 2015). You (2012) and Lail, Thomas, & Winterbotham (2013) stated that the quality of segment disclosure could be discretion by managers because of changes in segment aggressiveness, transfer of loads and other changes that are not visible.…”
Section: Hypotheses Developmentmentioning
confidence: 99%